The regulation of hypothalamic corticotropin-releasing factor release: in vitro studies. - Grossman, A; Costa, A; Navarra, P; Tsagarakis, S (1993)
Although there are various ways in which the regulation of hypothalamic corticotropin-releasing factor (CRF) may be investigated, the most direct is by the study of CRF secretion from rat hypothalami incubated in vitro. Using this technique, we have found stimulation of secretion by noradrenaline, acetylcholine, serotonin, neuropeptide Y, and interleukins 1 and 6; inhibitory modulation was shown by GABA, substance P, atrial natriuretic peptide, opioid peptides and precursors of nitric oxide. Studies of these interactions demonstrated certain non-linear characteristics which may allow appropriate mathematical models to be devised; this may aid in our understanding of clinical disorders associated with CRF excess.